Weather & Climate Services for the Energy Industry - Troccoli, Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This open access book showcases the burgeoning area of applied research at the intersection between weather and climate science and the energy industry. It illustrates how better communication between science and industry can help both sides. By opening a dialogue, scientists can understand the broader context for their work and the energy industry is able to keep track of and implement the latest scientific advances for more efficient and sustainable energy systems. Weather & Climate Services for the Energy Industry considers the lessons learned in establishing an ongoing discussion between the energy industry and the meteorological community and how its principles and practises can be applied elsewhere. This book will be a useful guiding resource for research and early career practitioners concerned with the energy industry and the new field of research known as energy meteorology.
1. Bridging the Climate-Energy Information Gap; Don Gunasekera -- 2. Achieving Valuable Weather and Climate Services; Alberto Troccoli -- 3. European Climate Services; Carlo Buontempo -- 4. What Does the Energy Industry Require From Meteorlogy?; Laurent Dubus, Shylesh Muralidharan and Alberto Troccoli 5. Forging A Dialogue Between the Energy Industry and the Meteorlogical Community; Alberto Troccoli et al. -- 6. Weather, Climate and the Nature of Predictability; David J. Brayshaw -- 7. Short-Range Forecasting For Energy; Sue Ellen Haupt -- 8. Medium and Extended Range Ensemble Weather Forecasting; David Richardson -- 9. Seasonal-To-Decadal Climate Forecasting; Emma Suckling -- 10. Regional Climate Projections; Robert Vautard; 11. The Nature of Weather and Climate Impacts in the Energy Sector; David J. Brayshaw -- 12. Probabilistic Forecasts for Energy - Weeks to a Century or More; John A. Dutton, Richard P. James and Jeremy D. Ross -- 13. Lessons Learned Establishing A Dialogue BetweenThe Energy Industry and The Metrological Community and A Way Forward; Laurent Dubus et al.
Keywords: Environment; Climatology; Energy policy; Energy and state; Environmental policy; Environmental Sciences; Climate Sciences; Energy Policy, Economics and Management; Environmental Policy